Clinical approaches to treat impaired awareness of hypoglycaemia - Catriona M. Farrell; Rory J. McCrimmon (Therapeutic Advances in Endocrinology and Metabolism, 2021)
Impaired awareness of hypoglycaemia (IAH) affects between 25% and 30% of all people with type 1 diabetes (T1D) and markedly increases risk of severe hypoglycaemia. This greatly feared complication of T1D impairs quality of life and has a recognised morbidity. People with T1D have an increased propensity to hypoglycaemia as a result of fundamental physiological defects in their ability to respond appropriately to a fall in blood glucose levels. With repeated exposure to low glucose, many then develop a condition referred to as IAH, where there is a reduced ability to perceive the onset of hypoglycaemia and take appropriate corrective action. The management of individuals with IAH relies initially on its identification in the clinic through a detailed exploration of the frequency of hypoglycaemia and an assessment of the individual’s ability to recognise these episodes. In this review article, we will address the clinical strategies that may help in the management of the patient with IAH once identified, who may or may not also suffer from problematic hypoglycaemia. The initial focus is on how to identify such patients and then on the variety of approaches involving educational programmes and technological approaches that may be taken to minimise hypoglycaemia risk. No single approach can be advocated for all patients, and it is the role of the health care professional to identify the clinical strategy that best enables their patient to achieve this goal.